Local Labour Market Resilience: The Role of Digitalisation and Working from Home - Sarra Ben Yahmed; Francesco Berlingieri; Eduard Brüll (CESifo GmbH, 2024)
We show that digital capital and working from home were essential for the resilience of local labour markets in the context of the COVID-19 crisis in Germany. Employment responses differed widely across local labour markets, with differences in short-time work rates of up to 30 percentage points at the beginning of the pandemic. Using recent advancements in the difference-in-differences approach with a continuous treatment, we find that pre-crisis digital capital potential reduced short-time work rate by up to 3 percentage points. The effect was nonlinear, disproportionately disadvantaging regions at the lower end of the digital capital distribution for a longer period. One channel of impact is working from home, which was more often adopted in regions with higher digital capital. But digital capital smoothed the employment shock beyond the effect of remote work.
Keywords: J21; O30; R12; R23; 330; Covid-19; crisis; digitalisation; employment; information and communication technologies; local labour markets; resilience; short-time work; working from home